Regional growth centres - the most attractive location in Finland? - Sari Pekkala (European Regional Science Association (ERSA), 2002)
The present study analyses migration patterns in Finland to test if micro- economic evidence for the Harris-Todaro model is found. The H-T hypothesis states that rural-urban migration is a results of differences in expected earnings and employment prospects. In addition to the basic framework factors such as distance-decay and human capital accumulation are considered. The recent migration trend in Finland show concentration of population in a handful of urban growth centres. Human capital is flowing towards those regions while rural areas are losing theirs. In recent years this tends has become more apparent, though the analysis of long-run trends shows that the urban pattern has been developing over several decades. Both the H-T hypothesis and the distance-decay hypothesis are supported by the data. Human capital (young, educated individuals) shows also greater concentration, as expected.
Keywords: 330